The proper functioning of the sense of smell and its disturbances on the example of COVID-19 infection - Kożuchowski, Marcin; Prylińska, Monika (Journal of Education, Health and Sport, 2022)
COVD-19 disease causes a wide range of respiratory symptoms. One of them is the olfactory disorder, which is also associated with other viral infections. Impaired sense of smell is associated with damage to the respiratory epithelium. Sniffing problems lasting longer than a few days are reported by more than half of patients infected with SARSCov-2 virus. This problem affects the quality of life and may result, among other things, in eating disorders or an increase in exposure to harmful chemicals. The olfactory epithelium, containing receptor cells, is primarily responsible for the proper functioning of the sense of smell. Impaired smell in COVID 19 is associated with damage to the respiratory epithelium. The article is a review of the scientific literature, in which the issues related to the physiology and anatomical structure of the olfactory organ and the influence of SARSCov-2 virus infection on olfactory disorders were discussed.